2020
DOI: 10.1056/nejmc2005073
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection in Children

Abstract: Globally 113 702 confirmed (4125 new) 4012 deaths (203 new) China 80 924 confirmed (20 new) 3140 deaths (17 new) Outside of China 32 778 confirmed (4105 new) 872 deaths (186 new) 109 countries/territories/ areas (5 new) WHO RISK ASSESSMENT China Very High Regional Level Very High Global Level Very High HIGHLIGHTS • 5 new countries/territories/areas (Brunei Darussalam, Mongolia, Cyprus, Guernsey and Panama) have reported cases of COVID-19 in the past 24 hours. 1 https://www.iatatravelcentre.com/international-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

187
2,504
39
278

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 2,301 publications
(3,008 citation statements)
references
References 2 publications
187
2,504
39
278
Order By: Relevance
“…The low rate of identified infection is somewhat surprising, as it is reasonable to assume that the pediatric patients with cancer would be at least as susceptible to infection with SARS-CoV-2 infection as their healthy peers. The SARS-CoV-2 does infect children in general, although lower severity of the infection makes children prone to be underreported 3,6 . Thus, at least in the countries with high COVID-19 incidence, either the transmission of SARS-CoV-2 was prevented by standard infection prevention measures, or cases remained undiagnosed as the course of the infection did not raise a suspicion of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low rate of identified infection is somewhat surprising, as it is reasonable to assume that the pediatric patients with cancer would be at least as susceptible to infection with SARS-CoV-2 infection as their healthy peers. The SARS-CoV-2 does infect children in general, although lower severity of the infection makes children prone to be underreported 3,6 . Thus, at least in the countries with high COVID-19 incidence, either the transmission of SARS-CoV-2 was prevented by standard infection prevention measures, or cases remained undiagnosed as the course of the infection did not raise a suspicion of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The mild disease experienced by the three children in this study is in direct contrast to the only previously published case of which we are aware. An 8 year old child undergoing myelosuppressive chemotherapy for T-cell acute lymphoblastic leukemia in ALL in a Wuhan hospital developed respiratory failure over the course of 3 weeks, eventually requiring mechanical ventilation; the patient had not recovered at the time of the report 8 (and included in 3,9 ). During the course of that patient's disease, CRP and IL-6 were only mildly elevated but ferritin levels were high (6417-15,758 ug/L).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elderly are the most vulnerable, and there is a high risk of exacerbation of psychic disorders and an aggravation of existing psychiatric symptoms, cognitive disorders and a loss of autonomy (Table 2). Children under 16 years of age seem to present less serious forms than adults (171 cases in China, average age of 6.7, 22 hospitalized cases of which 3 cases in intensive care) (15). In France, on the 26 th of March, a 16-year-old adolescent without comorbidities died from respiratory failure.…”
Section: Individual Vulnerability Of Psychiatric Patients To Coronavirusmentioning
confidence: 99%
“…Recent epidemiological reports also showed that the cases reported among children are relatively few and less severe [3]. Mainland China, which has the highest number of cases worldwide has reported that the mean age of pediatric patients with COVID-19 infection was 7 years old.…”
Section: Introductionmentioning
confidence: 99%